2023
DOI: 10.1021/jacs.3c01730
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of the Linaridin Pathway Provides Access to the Family-Determining Activity of Two Membrane-Associated Proteins in the Formation of Structurally Underestimated Cypemycin

Abstract: Cypemycin is a parent linaridin peptide known to contain nonproteinogenic dehydrobutyrine, N,N-dimethylalanine, and aminovinyl-cysteine residues. The enzymatic process by which this ribosomally synthesized peptide is formed remains elusive largely because of the deficiency of knowledge in post-translational modifications (PTMs) conducted by CypH and CypL, the two membrane-associated enzymes unique to linaridin biosynthesis. Based on heterologous reconstitution of the pathway in Streptomyces coelicolor, we repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 21 publications
1
24
1
Order By: Relevance
“…31,32 Recently, Liu et al deciphered the biosynthetic elucidation of one representative linaridin member cypemycin, revealing that two membrane-associated enzymes, CypH and CypL, were synergistically responsible for 16 reactions, including 11 epimerizations, 4 dehydrations, and 1 dethiolation. 33 Neither of the dethiolation mechanisms mentioned above appeared related to the glutamyl-tRNA Glu -dependent way of PsfB shown in this study.…”
Section: ■ Introductioncontrasting
confidence: 67%
See 2 more Smart Citations
“…31,32 Recently, Liu et al deciphered the biosynthetic elucidation of one representative linaridin member cypemycin, revealing that two membrane-associated enzymes, CypH and CypL, were synergistically responsible for 16 reactions, including 11 epimerizations, 4 dehydrations, and 1 dethiolation. 33 Neither of the dethiolation mechanisms mentioned above appeared related to the glutamyl-tRNA Glu -dependent way of PsfB shown in this study.…”
Section: ■ Introductioncontrasting
confidence: 67%
“…51 Recent studies by Liu et al identified that CypH and CypL are synergistically responsible for a series of 16 PTM reactions of cypemycin, including the dethiolation of Cys19, and exhibited high tolerance toward residues altering from Thr to Cys. 33 This enzymatic promiscuity may be attributed to the similar chemical properties of the sulfur and oxygen atoms. Dehydrated amino acids are among the most common unnatural amino acids in RiPPs and nonribosomal peptide synthetases.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of truncated MicA peptides, from 24-mer to 6-mer peptides, were examined, and all efficiently cyclized (Figures S21–25). Flavin-dependent cysteine decarboxylases usually display substrate tolerance toward peptides of diverse sequences. ,,,, Therefore, two short peptides with C-terminal cysteines but no sequence similarity to MicA, Pep-1 and Pep-2 , were synthesized by solid-phase synthesis and subjected to standard conditions. Both peptides were efficiently modified and cyclized (Figures S26 and 27).…”
mentioning
confidence: 99%
“…It is noteworthy that the catalytic mechanisms of these post-translational modifications (PTMs) are also distinguished from the biosynthesis of another class of dehydroamino acid-containing RiPPs, linaridins . Recently, Liu et al deciphered the cypemycin biosynthetic pathway, revealing that two membrane-associated enzymes, CypH and CypL, are synergistically responsible for not only the formation of characteristic Thr-derived dehydrobutyrines (Dhb) but also dethiolation and epimerizations . These enzymes appeared to be unrelated to the lanthipeptide biosynthetic machinery.…”
mentioning
confidence: 99%